Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1038/sj.npp.1301301
|View full text |Cite
|
Sign up to set email alerts
|

Supersensitivity to Amphetamine in Protein Kinase-C Interacting Protein/HINT1 Knockout Mice

Abstract: Protein kinase C interacting protein/histidine triad nucleotide binding protein 1 (PKCI/HINT1) is a member of the histidine triad protein family. Although this protein is widely expressed in the mammalian brain including mesocorticolimbic and mesostriatal regions, its physiological function in CNS remains unknown. Recent microarray studies reported decreased mRNA expression of PKCI/HINT1 in the frontal cortex of individuals with schizophrenia, suggesting the possible involvement of this protein in the pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 26 publications
3
56
1
1
Order By: Relevance
“…Some results did not reach statistical differences but had a trend of statistical differences, small samples may be one of the possible reason. Furthermore, in the OFT, there were no significant differences in the general locomotor activity of Hint1 ‐KO, ‐HT, and WT littermates, which were in line with the previous findings of Varadarajulua and colleagues, and Barbier and colleagues (Barbier et al., 2007; Varadarajulu et al., 2011). Interestingly, the mood behavior results found by Varadarajulua et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some results did not reach statistical differences but had a trend of statistical differences, small samples may be one of the possible reason. Furthermore, in the OFT, there were no significant differences in the general locomotor activity of Hint1 ‐KO, ‐HT, and WT littermates, which were in line with the previous findings of Varadarajulua and colleagues, and Barbier and colleagues (Barbier et al., 2007; Varadarajulu et al., 2011). Interestingly, the mood behavior results found by Varadarajulua et al.…”
Section: Discussionmentioning
confidence: 99%
“…CIS resulted in changes in emotional‐like behavior in Hint1 ‐KO (from the trend for anxiolytic‐like behavior to the elevated anxiety‐related behavior) and HT mice (from the trend of anxiolytic‐like and antidepression‐like behaviors, to the elevated anxiety‐related behavior and increased depression‐like behavior), may through other underlying molecular mechanisms. Barbier reported that absence of HINT1 may involve dysregulation of postsynaptic dopamine transmission (Barbier et al., 2007). It is possible that such variation in dopamine transmission may exert important role in HINT1‐related emotional‐like behaviors alterations after CIS; therefore, the molecular mechanism still needs further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Данный белок присутствует во всех тканях человеческого организма, но его наибольшая экспрессия характерна для головного и спинного мозга [9,25,26]. В результа-те экспериментальных исследований установлено, что большинство известных мутаций в гене HINT1 относятся к мутациям, приводящим к преждевременной терми-нации трансляции и, как следствие, к частичной потере функции белка [9].…”
Section: лечение и дальнейшее наблюдениеunclassified
“…Moreover, the levels of HINT1 are increased in brains from patients with major depressive disorder (28). A potential role of HINT1 in depression and anxiety disorders was also described in studies of HINT1 KO mice (2,3,42). Recently, using a combination of linkage analysis and next generation sequencing, Zimon et al (52) demonstrated that loss-of-function mutations in HINT1 cause axonal neuropathy with neuromyotonia.…”
Section: Hint1 Deficiency May Negatively Modulate Ca 2ϩ Signaling Viamentioning
confidence: 99%